The study of schoolchildren transportation efficiency in Lithuania - Lingaitis, Leonas P.; Bureika, Gintautas (Transport, 2003)
The system of Transportation of schoolchildren should also be transformed with the aim of more rational use of resources and vehicles taking children in and out of schools. Rational structure of school network and a system of children Transportation will help to save the money allocated on education as well as to ensure various educational services, taking into account social, economic, cultural and demographic changes. The research revealed considerable differences in operational costs of school buses in Lithuania. To account for this spread of values (up to 5 times), a more detailed analysis is needed. Considerable spread of operational costs of buses is questionable because they are m a good (or perfect) technical state. The repay time of the bus depends on the difference between the cost of carrying students by private and public transport covered by local government institutions and the relative expenses of busing a student per one kilometer by buses. First Published Online: 19 Dec 2011